Numerical Solution Of A Linear Goursat Problem Stability,Consistency And Convergence . - Md. Ismail, Ahmad Izani; Salim Nasir, Mohd Agos (2004)
The Goursat problem, associated with hyperbolic partial differential equations, arises in several areas of applications. These include mathematical modeling of reacting gas flows and supersonic flow.